(untitled) (Sains Humanika, 2011)
This study was designed to ascertain the quality of readiness in addressing meritocracy among lecturers and Malays students who attended Matriculation College, Ministry of Education. In particular, this study aims to find out if there are differences between lecturers’ and students’ perception in the eight domains related to meritocracy and achievement. The sample consists of 1800 students and 180 lecturers from seven Matriculation College, Ministry of Education, Malaysia. Data was collected using students’ and lecturers’ self-report questionnaires that comprise seven domains related to meritocracy which include concept of implementation, objective and effect of meritocracy, students learning, lecturers teaching and learning environment. Data was analysed using SPSS version 11. A one-way ANOVA, UNIVARIATE ANOVA and –t test were used in testing the research hypotheses. Pertinent results of the study indicate that there is a significant difference in the students’ mean scores on aspects of readiness based on previous schools. Significant differences are also identified in the mean scores of items related to lecturers’ readiness and their area of specilisation. The findings also show significance difference in the mean score between expectation, needs and constraints between students and lecturers. There are also significant differences of the items on quality, implication of commitment and motivation of students and lecturers in their readiness towards meritocracy. In summary, the results show differences in the students’ and lecturers’ perceptions in some aspects of readiness towards addressing meritocracy.